2018
DOI: 10.4047/jap.2018.10.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abutment diameter, luting agent type, and re-cementation on the retention of implant-supported CAD/CAM metal copings over short abutments

Abstract: PURPOSEThe aim of this study was to evaluate the effects of abutment diameter, cement type, and re-cementation on the retention of implant-supported CAD/CAM metal copings over short abutments.MATERIALS AND METHODSSixty abutments with two different diameters, the height of which was reduced to 3 mm, were vertically mounted in acrylic resin blocks with matching implant analogues. The specimens were divided into 2 diameter groups: 4.5 mm and 5.5 mm (n=30). For each abutment a CAD/CAM metal coping was manufactured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 28 publications
(42 reference statements)
3
21
0
2
Order By: Relevance
“…It could be shown that the pairwise comparisons had a post-hoc effect power ranging between 84% and 99%. The aging of the tested specimens for retention force evaluation was performed with HS and HTS that made the present study comparable to similar investigations [ 27 , 44 , 45 , 46 ]. Data from the present study clearly demonstrated that the bonding capacities of the various luting materials had a remarkable influence on the retention force only after the first cementation.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It could be shown that the pairwise comparisons had a post-hoc effect power ranging between 84% and 99%. The aging of the tested specimens for retention force evaluation was performed with HS and HTS that made the present study comparable to similar investigations [ 27 , 44 , 45 , 46 ]. Data from the present study clearly demonstrated that the bonding capacities of the various luting materials had a remarkable influence on the retention force only after the first cementation.…”
Section: Discussionsupporting
confidence: 66%
“…Mundt et al [ 30 ] used a similar sandblasting model of the cobalt–chromium crown inner surfaces with 50 mm particle size aluminum oxide at a pressure of 2.5 bar, followed by rinsing and drying, reporting similar observations. However, an in vitro study investigating the retention of implant-supported CAD/CAM metal copings after cementation with temporary cements and recementation with the permanent resin cement Panavia showed that the bond strength of the adhesive resins was not affected after minor surface alterations occurring during recementation [ 46 ]. The differences in the results can be explained by different study designs: the initial cementation was performed with temporary cement; however, the recementations were performed with temporary resin cements.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of retention of general prostheses is a method of measuring the pull force using a universal testing machine. 20 21 22 23 However, in this study, cement-retained implant prostheses with RCS measured force removed through lingual slots. These differences should be considered.…”
Section: Discussionmentioning
confidence: 94%
“…The results of this study show that the retentive force increases as the abutment height increases, and it is predictable that the surface area of abutment may also be affected. Previous studies 20 21 have suggested that abutment height has a significant effect on the resistance to removal. However, according to a follow-up study by Covey et al, 22 abutment height may be positively related to retention strength, but abutment's total surface area is not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation